The implication of emission control systems on the mass and energy balances of the kraft pulp mill process - A case study of Södra Cell Mönsterås’s recovery boiler - Johansson, Jesper; Olsson, Samuel (My University, 2024)
This master’s thesis concludes on the mass and energy balances of the kraft pulp mill process and investigates the possible implications in connection to new emis sion control systems. The work is based on a case study of the recovery boiler at Södra Cell in Mönsterås. Key aspects include the energy and element balances oc curring in the boiler and the emission of NOx and SOx . Three primary emission control measures are evaluated: injection of ammonia solutions (SNCR), injection of ammonia-containing gas (dissolver off gas), and the injection of scrubber effluent. The process model is based on previous work and validated by comprehensive data collection from the reference plant. The model is implemented in the software Aspen Plus. The model is zero-dimensional and equilibrium-based and cannot describe the effects of spatial distribution of air and temperature within the boiler or processes controlled by kinetic-based reactions. The result shows that the implementation of water-diluted ammonia injection with the potential to reduce NOx emissions by 45 % does not significantly affect flue gas temperature. While the use of dissolver off gas is advantageous, due to the utilisation of a waste stream, current ammonia levels from the dissolver off gas is insufficient for achieving significant SNCR effects compared to water-diluted am monia injection, with a difference of 0.69 mol NH3/s. Recycling scrubber effluent does not significantly alter the sulphidity of the flue gas but does increase reduction efficiency of the smelt, thereby reducing the need for make-up chemicals. The derived model is useful for describing the overall implications of the recovery boiler’s mass and energy balances and could be used to quantify the effects of other process modifications. The work should be complemented with more detailed design tools.
Keywords: Södra Mönsterås; kraftmassabruk; sodapanna; Aspen Plus; utsläppskontroll; primära åtgärder; NOx; SOx